Roles of nanomagnetic beads on biosensing: From fabrication to application - Junjie Li; Liyang Duan; Qian Chen; Songsong Huang; Weixia Li; Huachu Zuo; Shuang Li; Wei Han; Wei Fu; Shike Hou; Bin Fan; Zetao Chen (Interdisciplinary Medicine)
Abstract As magnetic nanomaterials, nanomagnetic beads are constantly being innovated in various applications. With the advantages of superparamagnetism and rapid magnetic response, nanomagnetic beads can be controlled for various type of movements under external magnetic fields, such as fixation, aggregation, or dispersion. Meanwhile, the nanomagnetic beads can be composited with multiple functional materials, therefore, expanding the applications in biomedical, environmental monitoring, and food safety. For example, the integration of nanomagnetic beads with magnetoresistive sensors can amplify the detection signals through the superparamagnetic properties. With the modification of recognition components, nanomagnetic beads can function by specifically binding target analytes, serving as sensitive elements for biosensing. In this review, we firstly summarized the fabrication approaches of nanomagnetic beads, supporting fundamental information for their applications. Then, roles of nanomagnetic beads in the field of biosensing were systematically discussed, such as sample preparation, sensitive elements immobilization, signal amplification, and sensitive detection. Through the investigation of nanomagnetic beads applications on biosensing, we finally evaluated current bottlenecks in the development of biosensors and predicted the future opportunities and challenges of biosensors based on the advancement of nanomagnetic beads.